Professional risks of the development of manufacturing disease in workers of the plating plant of the leading metallurgical enterprise - Lezhnina, M.; Sharavara, L. P.; Шаравара, Лариса Павлівна (My University, 2019)
To evaluate the professional risk of professional and industrial disease caused by melting shop to workers conductedan analysis of occupational diseases and morbidity with temporary disability for 4 years.We calculated key occupational risk indicators, such as relative risk (RR), attributive risk (AR), population attributive risk (PAR).It is determined that in the structure of occupational morbidity of workers 80% occupy respiratory diseases. According to figures calculated occupational risk set list of diseases that are conditioned production. Attributive risk of disease for workers repair shop was furnaces (AR 75,7%−37,7%), population attributive risk of disease for the control group (PAR 30,3%−7,8%).The data obtained confirm the need to introduce a system of preventive measures to reduce the incidence among the relevant category of workers.
Keywords: professional risk; professional disease; production-related morbidity